2015
DOI: 10.1177/1087054715584053
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Interventions in Children and Adolescents With ADHD: A Systematic Review

Abstract: At that time, no evidence-based recommendation can be formulated regarding frequency, intensity, or duration of exercise. Nevertheless, some first trends regarding the effects of certain types of exercise can be identified. When focusing on long-term health benefits in children and adolescents with ADHD, qualitative exercise characteristics might play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 83 publications
(202 reference statements)
3
76
0
5
Order By: Relevance
“…For reviews, see the following (Halperin, Berwid, & O’Neill, 2014; Neudecker, Mewes, Reimers, & Woll, 2015). Exercise appears to be particularly important for the normal development of executive function (Guiney & Machado, 2013; Hillman, 2014), a key driver of symptoms of inattention and disorganization in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…For reviews, see the following (Halperin, Berwid, & O’Neill, 2014; Neudecker, Mewes, Reimers, & Woll, 2015). Exercise appears to be particularly important for the normal development of executive function (Guiney & Machado, 2013; Hillman, 2014), a key driver of symptoms of inattention and disorganization in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of exercise on ADHD symptoms are reported to occur via dopaminergic and noradrenergic regulation, similar with the effects of stimulant medications which are the mainstay of ADHD treatment (Wigal et al 2013). However, it is not clear what type of exercise should be recommended, and there is no evidence-based definition of ideal frequency, intensity, or duration of exercise for patients with ADHD (Neudecker et al 2015).…”
Section: Exercise Addiction and Adhdmentioning
confidence: 99%
“…For example, in a recent study it was shown that a 6‐week intervention of cognitively demanding team games, but not a pure aerobic exercise intervention, had a positive effect on primary school children's EFs . Similarly, in children with ADHD, there seems to be evidence that mixed physical exercises (including multiple activities) might have the greatest potential to improve ADHD symptoms . Furthermore, this was highlighted in an influential review indicating that activities including physical and cognitive challenges might serve as treatment for ADHD .…”
Section: Introductionmentioning
confidence: 99%